2020
DOI: 10.1167/tvst.9.8.10
|View full text |Cite
|
Sign up to set email alerts
|

Chromatic Pupilloperimetry Measures Correlate With Visual Acuity and Visual Field Defects in Retinitis Pigmentosa Patients

Abstract: To evaluate the ability of chromatic pupilloperimetry to identify visual field (VF) defects in patients with retinitis pigmentosa (RP) and to test the correlation between pupilloperimetry impairment and retinal structural and functional measures. Methods: The pupil responses of 10 patients with RP (mean age, 41.3 ± 16.2 years) and 32 healthy age-similar controls (mean age, 50.7 ± 15.5 years) for 54 focal blue and red stimuli presented in a 24-2 VF were recorded. The pupilloperimetry measures were correlated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…The only latency-related parameter that had AUC-ROC < 0.7 for both eyes was the latency of maximal velocity (LMCV). Several studies indicated that the LMCV parameter differentiates with high specificity and sensitivity between healthy controls and patients with photoreceptor degeneration 36 , 38 . SD-OCT imaging for all participants included in the current study did not indicate any sign of photoreceptor degeneration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The only latency-related parameter that had AUC-ROC < 0.7 for both eyes was the latency of maximal velocity (LMCV). Several studies indicated that the LMCV parameter differentiates with high specificity and sensitivity between healthy controls and patients with photoreceptor degeneration 36 , 38 . SD-OCT imaging for all participants included in the current study did not indicate any sign of photoreceptor degeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Chromatic pupilloperimetry testing was performed as previously described 35 38 . Briefly, the device is comprised of a Ganzfeld dome apparatus with 76 LEDs (2 mm 2 diameter), an infrared camera and a fixation light.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The only latency-related parameter that had AUC-ROC <0.7 for both eyes was the latency of maximal velocity (LMCV). Several studies indicated that the LMCV parameter differentiates with high speci city and sensitivity between healthy controls and patients with photoreceptor degeneration 35,37 . SD-OCT imaging for all participants included in the current study did not indicate any sign of photoreceptor degeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Chromatic pupilloperimetry testing was performed as previously described 37 . Brie y, the device is comprised of a Ganzfeld dome apparatus with 76 LEDs (2 mm 2 diameter), an infrared camera and a xation light.…”
Section: Chromatic Pupilloperimetrymentioning
confidence: 99%